Design of a Compact CPW-Fed Monopole Antenna With Asymmetrical Hexagonal Slot Loaded Ground Structure for C/X/Ku Band Applications - Dwivedi, Ajay Kumar; Mishra, Brijesh; Singh, Vivek; Tripathi, Pramod Narayan; Singh, Ashutosh Kumar (Electrical, Control and Communication Engineering, 2020)
A novel design of ultra-wideband CPW-fed compact monopole patch antenna is presented in the article. The size of the antenna is 22 × 18 × 1.6 mm and it operates well over an ultra-wideband frequency range 4.86–13.66 GHz (simulated) and 4.93–13.54 GHz (measured) covering C, X and partial Ku band applications. The proposed design consists of a defected ground plane and U-shape radiating patch along with two square shape parasitic patches in order to achieve the ultra-wideband (UWB) operations. The performance matrix is validated through measured results that indicate the wide impedance bandwidth (93.2 %) with maximum gain of 4 dBi with nearly 95 % of maximum radiation efficiency; moreover, the 3D gain pattern manifests approximately omni-directional pattern of the proposed design. The prototype has been modelled using HFSS (High Frequency Structure Simulator-18) by ANSYS, fabricated and tested using vector network analyser E5071C.